2017
DOI: 10.1177/0886260517714437
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Child Sexual Abuse Discovery on Caregivers and Families: A Qualitative Study

Abstract: In this qualitative study with nonoffending caregivers of suspected child sexual abuse victims, we aimed to explore the perceived impact of sexual abuse discovery on caregivers and their families, and caregivers' attitudes about mental health services for themselves. We conducted semistructured, in-person interviews with 22 nonoffending caregivers of suspected sexual abuse victims <13 years old seen at a child advocacy center in Philadelphia. Interviews were audio-recorded, transcribed, coded, and analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…Nonoffending caregivers are primary supports for children who have been victims of CSA and the need for specific and tailored interventions for nonoffending caregivers is increasingly recognized in the literature and caregiver support has been identified as a crucial factors in children's recovery from CSA [32]. Caregiver interventions following sexual abuse of their child aim to reduce caregiver distress, increase adaptive caregiver coping as well as enhance support of the child [33]. Nonoffending caregivers have been referred to as "overlooked victims" in child sexual abuse cases [34].…”
Section: Interventions For Nonoffending Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonoffending caregivers are primary supports for children who have been victims of CSA and the need for specific and tailored interventions for nonoffending caregivers is increasingly recognized in the literature and caregiver support has been identified as a crucial factors in children's recovery from CSA [32]. Caregiver interventions following sexual abuse of their child aim to reduce caregiver distress, increase adaptive caregiver coping as well as enhance support of the child [33]. Nonoffending caregivers have been referred to as "overlooked victims" in child sexual abuse cases [34].…”
Section: Interventions For Nonoffending Caregiversmentioning
confidence: 99%
“…Nonoffending caregivers have been referred to as "overlooked victims" in child sexual abuse cases [34]. A recent qualitative study with nonoffending caregivers of children under 13 who had been victims of CSA found that the majority of caregivers reported mental health services were necessary and beneficial for themselves to help them cope with the impact of their child's CSA [33]. Interventions for nonoffending caregivers may include group and/or individual treatment focusing on psychoeducation, information, supports, parenting guidance, and dealing with their own victimization (if relevant).…”
Section: Interventions For Nonoffending Caregiversmentioning
confidence: 99%
“…Some caregivers find their child's traumatic stress symptoms to be a traumatic experience for themselves. Many experience significant amounts of emotional and psychological distress (Fong et al, 2020), with the potential for the caregivers to develop their own posttraumatic stress symptoms (E. Cohen, 2008;Saltzman et al, 2008). Nonoffending caregivers often experience their child's abuse as psychologically traumatic, with specific sources of distress including concerns about the child, and their parenting abilities, and the reactions and actions of the family system (Fong et al, 2020;Ford & Saltzman, 2009).…”
Section: Caregiver Support As a Mediating Factormentioning
confidence: 99%
“…Future research that explores the experiences of caregivers would contribute essential perspectives to our understanding of caregiver challenges and effective strategies. Fong et al (2020) interviewed nonoffending caregivers, exploring the impact their child's abuse had on them and their families. Their findings stress the emotional and psychological impact the abuse has on caregivers and the family system, but also highlight that caregivers see the usefulness in their own mental health support and desire to receive services.…”
Section: Implications For Social Work Practicementioning
confidence: 99%
“…The increasing cases of sexual violence can have a negative impact on victims, such as physical and psychological damage in the form of mental trauma, depression (Wheeler & McElvaney, 2017). Behaviors of sexual violence in children with physical or emotional abuse can impact the development of sexual behavior and aggression that are harmful to the child's Future (Fong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%